The Actualization And Transformation Of Shame Culture In The Siulak Mukai Indigenous Community: An Ethnographic Study - Wawan Septian; Oki Mitra; Wisnarni; Muhammad Alfian (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study investigates the concept of malu (shame) within the Siulak Mukai indigenous community of Kerinci, to understand its meanings, values, and functions, as well as examine how it is actualized in daily life and transformed in the context of modernization and digital culture. Adopting a qualitative descriptive design with an ethnographic approach, data were collected through observations, semi-structured interviews, and documentation involving customary leaders, elders, and community representatives. The findings reveal that malu functions as a moral and social safeguard, regulating behavior, preserving personal dignity, and maintaining social cohesion. Its actualization is gendered: for boys, it is expressed through responsibilities as protectors and educators within the clan, while for girls, it is reflected in safeguarding personal and familial honor. The intergenerational transmission of malu is sustained through customary education by ninik mamak, teganai, and depati using advice, metaphors, and communal practices. However, the study also identifies significant erosion of malu among younger generations, influenced by globalization, social media, and the weakening role of traditional leaders. This research contributes to the understanding of indigenous moral systems by demonstrating how shame culture, despite facing decline, remains a central ethical and cultural value that underpins social cohesion and identity in Siulak Mukai. The originality of this study lies in highlighting the transformative challenges of malu in the digital age and proposing culturally grounded strategies for its revitalization through customary institutions, intergenerational education, and integration into formal schooling.